Native plant community response to alien plant invasion and removal - Jara ANDREU; Montserrat VILÀ (Management of Biological Invasions, 2011)
Given the potential ecological impacts of invasive species, removal of alien plants has become an important management challenge and a high priority for environmental managers. To consider that a removal effort has been successful requires both, the effective elimination of alien plants and the restoration of the native plant community back to its historical composition and function. We present a conceptual framework based on observational and experimental data that compares invaded, non-invaded and removal sites to quantify invaders’ impacts and native plant recover after their removal. We also conduct a meta-analysis to quantitatively evaluate the impacts of plant invaders and the consequences of their removal on the native plant community, across a variety of ecosystems around the world. Our results that invasion by alien plants is responsible for a local decline in native species richness and abundance. Our analysis also provides evidence that after removal, the native vegetation has the potential to recover to a pre-invasion target state. Our review reveal that observational and experimental approaches are rarely used in concert, and that reference sites are scarcely employed to assess native species recovery after removal. However, we believe that comparing invaded, non-invaded and removal sites offer the opportunity to obtain scientific information with relevance for management.